Reparation of nano-FeS by ultrasonic precipitation for treatment of acidic chromium-containing wastewater - Mengjia Dai; Junzhen Di; Ting Zhang; Tuoda Li; Yanrong Dong; Sihang Bao; Saiou Fu (Scientific Reports, 2024)
Abstract Nano-FeS is prone to agglomeration in the treatment of chromium-containing wastewater, and ultrasonic precipitation was used to synthesize nano-FeS to increase its dispersion. The optimization of the preparation method was carried out by single factor method (reaction temperature, Fe/S molar ratio and FeSO4 dropping flow rate) and response surface methodology. Dynamic experiments were constructed to investigate the long-term remediation effect and water column changes of nano-FeS and its solid particles. The changes of the remediation materials before and after the reaction were observed by SEM, and the mechanism of the remediation of chromium-containing wastewater by nano-FeS prepared by ultrasonication was revealed by XRD. The results showed that the reaction temperature of 12 °C, Fe/S molar ratio of 3.5 and FeSO4 dropping flow rate of 0.5 mL/s were the best parameters for the preparation of nano-FeS. The nano-FeS has efficient dispersion and well-defined mesoporous structure in the form of needles and whiskers of 40–80 nm. The dynamic experiments showed that the average removal of Cr(VI) and total chromium by nano-FeS and its immobilized particles were 94.97% and 63.51%, 94.93% and 45.76%, respectively. Fe2+ and S2− ionized by the FeS nanoparticles rapidly reduced Cr(VI) to Cr(III). Part of S2− may reduce Fe3+ to Fe2+, forming a small iron cycle that gradually decreases with the ion concentration. Cr(III) and Fe2+ form Cr(OH)3 and FeOOH, respectively, with the change of aqueous environment. Another part of S2− reacts with Cr(III) to form Cr2S3 precipitate or is oxidized to singlet sulfur. The FeS nanoparticles change from short rod-shaped to spherical shape. Compared with the conventional chemical precipitation method, the method used in this study is simple, low cost, small particle size and high removal rate per unit.